PROJECT BASED- LEARNING IN TEACHERS’ PERSPECTIVES - Trisdiono, Harli (Dewantara, 2014)
This study was conducted to determine the teacher 's perspective of project -based learning in Special Region of Yogyakarta. This study is a qualitative research. It describes the teachers? perceptions on project based learning.The data was taken from the sample of 34 teachers through observation, interviews and questionnaires. The perspective of teachers of the learning experience planning constraints on the determination of teaching material according to curriculum implemented using project based learning. In the implementation of the teachers had difficulty in terms of time as project based learning takes a long time, and others feared to disturb the learning process. In terms of assessment, teachers have difficulty doing authentic assessment in the learning process and learning outcomes, especially in the realm of attitudes and skills.The project based learning can improve students' skills in integrating the achievement of competence in the areas of attitude, knowledge, and skills, but requires the readiness of teachers in the planning and control of the time so that the learning can be done well, and students can attain competency knowledge.